2019
DOI: 10.3390/app9071389
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Climate Conditions on Deficiencies of Building Roofs

Abstract: Climate conditions affect buildings’ performance and durability. The purpose of this paper is to examine the influence of climate conditions on roof deficiencies. 763 cases of such deficiencies were analyzed in this regard. Once the construction deficiencies were quantified, they were characterized from a climatological point of view and their ‘climate location segments’ were studied to obtain ‘ranges of concentration of anomalies’ according to the obtained percentage. A direct relation is shown to exist betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 22 publications
0
1
0
Order By: Relevance
“…These parameters can include budget limitations, aesthetic appearance, desired condition level, local constraints, environmental exposure conditions, and the social and economic contexts of the building. Furthermore, based on the identified common relation between maintenance needs and design errors, the components' maintainability requirements and degradation performance are not always known to the building designers [23]. Frequently, the maintainability of the material is not a priority, which compromises the future maintenance activities and the costs throughout the service life [19].…”
Section: Introductionmentioning
confidence: 99%
“…These parameters can include budget limitations, aesthetic appearance, desired condition level, local constraints, environmental exposure conditions, and the social and economic contexts of the building. Furthermore, based on the identified common relation between maintenance needs and design errors, the components' maintainability requirements and degradation performance are not always known to the building designers [23]. Frequently, the maintainability of the material is not a priority, which compromises the future maintenance activities and the costs throughout the service life [19].…”
Section: Introductionmentioning
confidence: 99%
“…Those judicial files were selected due to the filing of demands by building users against agents participating in the construction process, as a result of failures existing in construction elements in the buildings -namely, in this case, in internal partition walls. The failures detected between the years 2008 and 2017 and which resulted in subsequent demands were considered in this study [50]. In order to be able to include cases in the research, an additional condition was set, that the demands in question were already concluded and unappealable (their sentence was final and could not be appealed/sent to higher courts).…”
Section: Methodsmentioning
confidence: 99%